PENDUGAAN MODEL PERAMALAN HARGA DAN INTEGRASI PASAR SPASIAL KACANG TANAH - Sakinah, Fitri; sukiyono, ketut; Reswita, Reswita (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2018)
This research is aimed at examining the best forecasting model for peanut price and analyzing the spatial market integration of peanuts in Bengkulu province. Monthly data of peanut from 2004:1 – 2013:12 are used for this research and three trend model, i.e., linear, quadratic and exponential trend are applied in which the selection of the best model is based on the lowest value of MAPE, MAD, and MSD. The VAR model of market integration is applied and combined with cointegration and Granger Causality test. This research finds that the best forecasting model is quadratic trend model. This research also concludes that spatial market of peanuts in Bengkulu has already well integrated and each district interplays a peanut price.